The Impact of Implementing Digital Technology Through the Quizziz and Kahoot Applications on Student Learning Outcomes - Putra, Chandra Anugrah; Wati, Ida (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This article aims to analyze the use of the quizziz application and the kahoot application with a focus on how these applications can be used to improve student learning outcomes in the digital era.This research uses a qualitative descriptive approach, with the observation method as the research framework. Data was collected from several classes that have successfully integrated the Quizziz and Kahoot applications into the learning process. This study explores various aspects of technology implementation, Including the types of applications used, the training provided to teachers, and its impact on student independence and learning outcomes. Data was collected through in-depth interviews with teachers and students as well as participatory observation in classes that have implemented the Quizziz and Kahoot applications in classroom learning can improve student learning outcomes.